DPP-4 inhibition has beneficial effects on the heart after myocardial infarction. (February 2016) - Kubota, Akihiko; Takano, Hiroyuki; Wang, Haixiu; Hasegawa, Hiroshi; Tadokoro, Hiroyuki; Hirose, Masanori; Kobara, Yuka; Yamada-Inagawa, Tomoko; Komuro, Issei; Kobayashi, Yoshio
Abstract: Aims: Dipeptidyl peptidase-4 (DPP-4) inhibitors are reported to have protective effects on various cells but it is unclear how DPP-4 inhibitors have cardioprotective effects. Our aim was to study the mechanisms of cardioprotective effects by DPP-4 inhibition. Methods and results: C57BL/6 mice and DPP-4 knockout (DPP-4KO) mice were subjected to left coronary artery ligation to produce acute myocardial infarction (MI). C57BL/6 mice were then treated with vehicle or DPP-4 inhibitor. Left ventricular function, infarct size, the number of vessels, and myocardial ischemia were assessed at 5 days after MI. The treatment with DPP-4 inhibitor significantly improved cardiac function and decreased the infarct size. DPP-4 inhibitor increased the ratio of endothelial cell numbers to a cardiomyocyte. The extent of myocardial ischemia and the number of TUNEL-positive cells in the border area were significantly decreased by DPP-4 inhibitor. Stromal cell-derived factor-1α (SDF-1α) level in myocardium was significantly increased by DPP-4 inhibitor. Those cardioprotective effects after MI were also recognized in DPP-4KO mice. DPP-4 protein was expressed on rat neonatal cardiomyocytes and DPP-4 inhibitor significantly reduced hypoxia-induced apoptosis in the cardiomyocytes. However, this effect was abolished by the pretreatment with a CXCR4 antagonist or a signal transducer and activator of transcription 3 (STAT3) inhibitor. The beneficial effects of DPP-4 inhibitor on heart failure after MI were abolished by cardiomyocyte-specific deletion of STAT3. Conclusions: DPP-4 inhibition may have direct protective effects on the post-MI heart by inducing an antiapoptotic effect and inhibiting a decrease in vessel number through the SDF-1α/CXCR4-mediated STAT3 signaling pathway. Highlights: DPP-4 inhibition improved cardiac function and decreased the infarct size after MI. DPP-4 inhibition prevented apoptosis of cardiomyocytes after MI. The effects of DPP-4 inhibition were mediated through STAT3 pathways in cardiomyocytes.